A Peace Award Nomination Triggered by Butterfly Effect of Chaos Theory: A Case Report - Salerian, Alen J (European Journal of Applied Sciences, 2026)
This report presents a proposed peace award nomination for six scholars in Norway, inspired by Vanessa M’s prayer in Clintwood, Virginia consistent with the butterfly effect of chaos theory: A case report. Edward Lorenz an American meteorologist discovered the underlying mechanism of deterministic chaos and complexity. 1. 11/20/24 : 4 WHD members pray “Vanessa M’s prayer”. 2. 02/15/2025 :Discover Silenced Heroes Conference and Exhibition at Ritz Carlton in New Orleans. 586 people registered. 3. 02/27/2025 The City Council of New Orleans proclaimed September 15th, 2021 the World Honesty Day.. 4. 09/21/2025 World Honesty Day.,.New Orleans, Istanbul, Lagos NIGERIA Trinity House performed Beethoven’s Ode to Joy ,live. 5. A proposal for a major peace award for 6 peace scholars. Human behavior is governed by physical laws with sensitive dependence on Initial biological conditions (2). Exponentially magnified positive or negative outcome may correspond to the Initial biological conditions. Catastrophic wars and genocide may emerge from initial presidential misjudgments and lies :2nd ww, Coup D’etat. Good will prayers may trigger greatly magnified influence to promote peace.